Pemanfaatan Sosial Media Sebagai Wujud Inovasi Dalam Pelayanan Publik Oleh Ombudsman Ri Bengkulu - Fitria Yuliani; Rekho Adriadi; Linda Safitra (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
The use of social media today is not only functioned for personal interests, but also for the benefit of groups, organizations, and state institutions in terms of public services as conducted by the Ombudsman RI Bengkulu who utilize social media as a medium of public service in Bengkulu province. It is interesting to study about the new "concept" that is applied in the process of public service, especially one of the challenges that faced by these institutions is the lack of public understanding of the existence of these institutions, so that innovation is basically needed in reaching out to the community and carrying out the role as a state institution with totality in carrying out public services as an objective of the existence of this state institution. This research was conducted to see how the social media was utilized by Ombudsman RI Bengkulu in conducting public services as a form of innovation in public service by Ombudsman RI Bengkulu. The research method was using a qualitative descriptive approach where the research results were analyzed by using the theory of diffusion of innovations. The research subjects in this case are the Ombudsman RI Bengkulu, and the social media users who have accessed the Ombudsman RI Bengkulu social media page, which is proven by digital traces left in the form of likes and comments on the Ombudsman RI Bengkulu Social media. The four elements in the innovation diffusion process show the innovations that applied in the public service process by the Ombudsman RI Bengkulu and how the utilization of these innovations in the public service process by the Ombudsman RI Bengkulu. Innovation in this regard is related to the use of social media as a medium for socialization and raising complaints in the process of public service by the Ombudsman RI Bengkulu. It is said as a form of innovation because the process of public services that is usually done traditionally both directly and through traditional media so that it costs quite a lot, with the use of social media can be done more easily, quickly and efficiently.Â Keywordsâ€”: Innovation; Service; Public; Social Media; Ombudsman RI Gender Bengkulu.